Production of Cryoprecipitate of Intermediate Purity in a Closed System Thaw-Siphon Process - Mason, Ernest C; Pepper, Duncan S; Griffin, Brenda (Thrombosis and Haemostasis, 1981)
The thaw-siphon procedure for routine production of cryoprecipitate is described briefly, and also its extension to a reproducible procedure for production of cryoprecipitates of intermediate purity. For the latter, the average yield of factor VIII is 60% of that in the prefrozon plasma and approximately 30% is present in the supernatant plasma. The product contains 0.53 units of VIII:C per mg of total protein (of which about 70% is clottable). The mean value of the ratio VIII:C/VIII:RAG is about 0.7. The yield and purity of the product compare favourably with those reported for intermediate purity factor VIII concentrates produced by large-scale plasma fractionation laboratories. The procedure offers an alternative pathway to the production of factor VIII concentrate of intermediate purity and can be operated in any blood bank with a minimum of equipment.
Keywords: F VIII: C; Cryoprecipitation; Thaw-siphon